Biocarbón a partir del raquis de banano aplicando adsorción en columna para la recuperación de itrio en soluciones acuosas. - Piñancela Márquez, Kerly Yuliana; Armijos Aguilar, Diego Alexander (My University, 2025)
This research evaluated the use of biochar obtained from banana stems as an adsorbent material for the recovery of yttrium (Y³⁺) in aqueous solutions. The precursor material from banana stems was synthesized by incorporating PEG and CMC and subjected to a pyrolysis process at 800°C, thus obtaining biochar with properties suitable for adsorption studies. The banana stem biochar (BRB) was characterized by FTIR spectroscopy and proximate analysis to determine moisture, ash, volatile matter, and fixed carbon. Its yttrium adsorption capacity was evaluated at pH 4 and 5, as well as its selectivity against rare earths and heavy metals. In addition, column tests were performed to study continuous-flow adsorption. Desorption studies were also conducted with different reagents at temperatures of 25°C and 80°C to determine yttrium recovery efficiency. The experimental study was carried out at pH 5, obtaining a higher adsorption capacity (55.09 mg/g); however, pH 4 was used to prevent Y³⁺ precipitation. Selectivity with rare earths showed greater affinity toward Neodymium, with an adsorption capacity of 35.45 mg/g; and among heavy metals, the BRB showed high selectivity toward Yttrium, with an adsorption capacity of 40.30 mg/g. In the fixed-bed column study, breakthrough times were 4 hours at a flow rate of 0.05 L/h, while at a flow rate of 0.01 L/h, the path time was 39 hours, indicating that a lower flow rate results in greater adsorption by the BRB. Desorption was limited to a single cycle. At a temperature of 25°C, the best desorbent was hydrochloric acid (HCl), and at a temperature of 80°C, the best desorbent was aluminum sulfate (Al2(SO4)3). These results demonstrate that biochar derived from banana agro-industrial waste can be a sustainable alternative for the recovery of elements such as yttrium, promoting the circular economy.
Esta investigación se evaluó el uso de biocarbón obtenido a partir del raquis de banano como material adsorbente para la recuperación de itrio (Y³⁺) en soluciones acuosas. El material precursor a partir de raquis de banano se sintetizó mediante la incorporación de PEG y CMC, sometido a un proceso de pirólisis a 800 °C, obteniendo así el biocarbón con propiedades adecuadas para estudios de adsorción. El biocarbón de raquis de banano (BRB) fue caracterizado mediante espectroscopía FTIR y análisis proximal para determinar humedad, cenizas, materia volátil y carbono fijo. Se evaluó su capacidad de adsorción de itrio a pH 4 y 5, así como su selectividad frente a tierras raras y metales pesados. Además, se realizaron ensayos en columna para estudiar la adsorción en flujo continuo. También, se llevaron a cabo estudios de desorción con diferentes reactivos a temperaturas de 25 °C y 80 °C para determinar la eficiencia en la recuperación del itrio. El estudio experimental realizado a pH 5 obtuvo mayor capacidad de adsorción (55.09 mg/g), sin embargo, se utilizó pH 4 para evitar la precipitación de Y³⁺. La selectividad con tierras raras mostró mayor afinidad hacia Neodimio con una capacidad de adsorción de 35.45 mg/g; y entre los metales pesados, el BRB presentó alta selectividad hacia Itrio con una capacidad de adsorción de 40.30 mg/g. En el estudio de columna de lecho fijo, los tiempos de ruptura fueron de 4 horas a un caudal de 0.05 L/h, mientras que para un caudal de 0.01 L/h el tiempo de ruta de fue de 39 horas, lo que indica que a menor flujo existe mayor adsorción del BRB. La desorción fue limitada en un solo ciclo, a una temperatura de 25°C el mejor desorbente es el ácido clorhídrico (HCl) y a una temperatura de 80 °C el mejor desorbente es el sulfato de aluminio (Al2(SO4)3). Estos resultados evidencian que el biocarbón derivado de residuos agroindustriales del banano puede ser una alternativa sustentable para la recuperación de elementos como el itrio, favoreciendo la economía circular.
Keywords: BIOCARBÓN; PIROLISIS; ADSORCIÓN; ITRIO